A Review of Intelligent Models for Gas Well Productivity Prediction and Production Optimization - Tian, Chenhao; Huang, Yongxiang; Wang, Shaonan; Li, Chenjun (Scientific Journal of Technology, 2026)
Natural gas, as a clean and efficient energy source, occupies an increasingly important position under the background of the "dual-carbon" strategy and energy structure transformation. However, affected by various complex factors such as reservoir heterogeneity, gas-liquid-solid multiphase flow, inter-well interference, and lack of bottom-hole pressure, traditional gas well productivity prediction and production allocation methods have problems such as insufficient accuracy, poor adaptability, and high dependence on manual work, making it difficult to meet the needs of efficient development of offshore and unconventional gas reservoirs. Therefore, to meet the requirements of accuracy, adaptability, and intelligence, this paper studies the intelligence of gas well productivity prediction and its production allocation model, analyzes and compares current machine learning algorithms such as XGBoost, Random Forest, Support Vector Machine (SVM), and Long Short-Term Memory Neural Network (LSTM) in gas well dynamic analysis, points out the existing problems in current research, and looks forward to the development trends of gas well productivity prediction and production allocation in the directions of multi-factor coupling, intelligent integration, and full-life-cycle dynamic optimization.